Economic production quantity model with defective items, imperfect rework process, and lost sales - Chusnul Aprilianti; Annisa Kesy Garside; Amelia Khoidir; Thomy Eko Saputro (Universitas Serang Raya, 2024)
This study proposes an economic production quantity (EPQ) model that comprehensively addresses scrap items, imperfect quality items, rework processes, and shortages. The model incorporates various types of defective items, including scrap, imperfect quality, and rework able items, and implements immediate rework processes upon the completion of regular production. Shortages are treated as lost sales, enhancing the accuracy of inventory cost estimations. Numerical experiments demonstrate the optimality of production lot sizes and underscore the impact of production and demand rate adjustments on overall inventory costs. Sensitivity analysis further elucidates the influence of imperfect quality items on inventory costs. This EPQ model offers a comprehensive approach to efficient and effective finished product inventory management by integrating considerations for scrap items, imperfect quality items, and rework processes. Additionally, a furniture manufacturing company case is presented to illustrate the practical application of the proposed model.